Randomised controlled trials for improving health outcomes for people living with multiple long-term conditions: Protocol for a systematic review of methodological approaches, risk of bias and reporting quality - Lisong Zhang; Elizabeth Fisher; Naomi Bradbury; Natalie Darko; Kamlesh Khunti; Selina Lock; Sally J. Singh; Sharon A. Simpson; Ellesha Smith; Susan M. Smith; Rod S. Taylor; Miles Witham; et al. (PLoS ONE, 2025)
Introduction The number of people living with multiple long-term conditions (MLTC or multimorbidity) is increasing. There have been national and international calls for more and better research in this clinical area. This systematic review will assess the methodological approaches, risk of bias and standards of reporting of the included trials. This study will benchmark current methodological practice and identify areas for improvement. Methods and analysis MEDLINE, Scopus, CINAHL, CENTRAL and the International Research Community in Multimorbidity database will be searched from January 1999 to identify randomised controlled trials conducted with the aim of improving health outcomes for people living with MLTCs. Study screening, data extraction and the risk of bias assessment will be conducted independently by two reviewers. Data to be extracted will include study descriptors, design and analysis characteristics, methodological quality, bias and standard of reporting. A narrative synthesis will be conducted to summarise current methodological practice and to identify areas for improvement. Ethics and dissemination Ethical approval is not required. The results of the review will be published in a peer-reviewed journal and shared via conferences and webinars. PROSPERO registration number: CRD42024595925